Autonomy and Power : the Dynamics of Class and Culture in Rural Bolivia - Lagos, Maria L. (Philadelphia, Pa. : University of Pennsylvania Press, 2016)
Maria L. Lagos supplies a fine-grained ethnographic and historical analysis of the intersecting dynamics of class and culture in Tiraque, a province in the highlands of Cochabamba, Bolivia.
Frontmatter -- Contents -- Illustrations -- Abbreviations -- Preface -- Introduction -- 1. An Introduction to Tiraque -- 2. The Emergence of a Merchant Class and Landowning Peasants -- 3. Revolution, Agrarian Reform, and the State -- 4. Production, Sharecropping, and Class -- 5. The Accumulation of Wealth and Capital -- 6. The Culture of Power and Politics -- Conclusion: The Paradoxes of Autonomy, Power, and Culture -- Appendix: Bolivian Exchange Rates, 1982-85 -- Notes -- Glossary -- References -- Index -- Backmatter
In English.
Online resource; title from PDF title page (publisher's Web site, viewed Dec. 09, 2016).
JSTOR
Keywords: Indians of South America -- Bolivia -- Tiraque (Cordillera) -- Politics and government; Indians of South America -- Land tenure -- Bolivia -- Tiraque (Cordillera); Indians of South America -- Bolivia -- Tiraque (Cordillera) -- Social conditions; Peasants -- Bolivia -- Tiraque (Cordillera); Rural poor -- Bolivia -- Tiraque (Cordillera); Tiraque (Cordillera, Bolivia) -- History; Tiraque (Cordillera, Bolivia) -- Social conditions; Tiraque (Cordillera, Bolivia) -- Politics and government; SOCIAL SCIENCE -- Anthropology -- General; Indians of South America -- Land tenure; Indians of South America -- Politics and government; Indians of South America -- Social conditions; Peasants; Politics and government; Rural poor; Social conditions; Bolivia -- Tiraque (Cordillera); History